Observed variability of intertropical convergence zone over 1998—2018. (18th September 2020) - Liu, Chunlei; Liao, Xiaoqing; Qiu, Juliao; Yang, Yazhu; Feng, Xiaoli; Allan, Richard P; Cao, Ning; Long, Jingchao; Xu, Jianjun
Abstract: The intertropical convergence zone (ITCZ) accounts for more than 30% of the global precipitation and its variability has a great effect on the people living in the tropical area. It is the manifestation of the Hadley circulation, tropical dynamic and thermodynamic coupling and the air-sea interaction. Therefore, it is essential to understand the changes and variability of the ITCZ, including its position and intensity. Using observed precipitation from GPCP and TRMM 3B43, as well as the ERA5 reanalysis data, we examine the ITCZ variations over the global and seven regions from 1998–2018. These data sets show consistent ITCZ climatology and inter-annual variability. Except over Atlantic and eastern Pacific where ITCZ stays in the northern hemisphere, the ITCZ crosses the equator after equinoxes over other sections. There is no overall significant shift of annual mean ITCZ position over the globe and seven regions, except over the America section where the GPCP data show a significant increase trend of 0.8° decade −1 and over the western Pacific section where ERA5 data show a significant decrease trend of −1.2° decade −1 . The ITCZ positions over the globe and Africa are related to both ENSO and NAO, while ITCZ position over eastern Pacific is significantly affected by ENSO and the Atlantic ITCZ is mainly related to NAO. Except for the western Pacific, all other sections are significantly related to local meridional surface temperature gradient, particularly over America, Atlantic and eastern Pacific. The meridional gradient variation of the vertically integrated moist static energy has generally good agreement with the shift of the intertropical convergence zone, particularly for the seasonal climatology over the Africa region. The relationship between ITCZ position and intensity shows complicated patterns, with positive correlation over the globe, but different correlations over different sections. The two observed data sets are more or less consistent, but ERA5 shows discrepancies over some sections. It is also found that the local meridional temperature gradient has more influences on the ITCZ positions than the global one.